Wellness Swimming as a Part of the Physical Education of Students - Kayumovna, Ruziyeva Mahliyo (European Journal of Life Safety and Stability (2660-9630), 2022)
This article presents the main tasks and the role of recreational swimming in the field of physical education. Recreational swimming is considered by the author as a part of the physical education system of higher educational institutions. The scheme of distribution of students to medical groups is described, some recommendations are given for conducting classes by semesters. Also, the author focuses on the formation of classes for students of the special department. The article is intended as theoretical material for students and teachers of higher educational institutions.